Prenatal Programming of Pulmonary Hypertension Induced by Chronic Hypoxia or Ductal Ligation in Sheep. (1st December 2013) - Papamatheakis, Demosthenes G.; Chundu, Madalitso; Blood, Arlin B.; Wilson, Sean M.
Abstract : Pulmonary hypertension of the newborn is caused by a spectrum of functional and structural abnormalities of the cardiopulmonary circuit. The existence of multiple etiologies and an incomplete understanding of the mechanisms of disease progression have hindered the development of effective therapies. Animal models offer a means of gaining a better understanding of the fundamental basis of the disease. To that effect, a number of experimental animal models are being used to generate pulmonary hypertension in the fetus and newborn. In this review, we compare the mechanisms associated with pulmonary hypertension caused by two such models: in utero ligation of the ductus arteriosus and chronic perinatal hypoxia in sheep fetuses and newborns. In this manner, we make direct comparisons between ductal ligation and chronic hypoxia with respect to the associated mechanisms of disease, since multiple studies have been performed with both models in a single species. We present evidence that the mechanisms associated with pulmonary hypertension are dependent on the type of stress to which the fetus is subjected. Such an analysis allows for a more thorough evaluation of the disease etiology, which can help focus clinical treatments. The final part of the review provides a clinical appraisal of current treatment strategies and lays the foundation for developing individualized therapies that depend on the causative factors.